2009
DOI: 10.1088/0953-8984/21/4/046004
|View full text |Cite
|
Sign up to set email alerts
|

Study of the size-dependent properties of ScnAl (n= 1–14) clusters by density-functional theory

Abstract: The geometries, stabilities, and electronic and magnetic properties of Sc(n)Al (n = 1-14) clusters with different spin configurations have been investigated systematically within the framework of the gradient-corrected density-functional theory. Our resulting geometries show that the aluminum atom remains on the surface of clusters with n<9, while it takes up the center of Sc-cage clusters with n≥9. Besides, the doping of Al improves the stability of the host clusters. Maximum peaks are observed for Sc(n)Al cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…During the last few decades, the binary clusters have attracted considerable attention of a wide range of researchers. Theoretical and experimental studies have demonstrated that the nature of the cluster can be altered significantly with the addition of a single impurity atom. , Doping of gold clusters with an impurity atom has been actively sought to tailor the desired structural, electronic, catalytic, and magnetic properties for potential applications in nanotechnology, microelectronics, solid-state chemistry, and materials science. For example, Zhang et al proved that doping with different 3p impurity atoms (Al, Si, P, S, and Cl) can strongly influence the structure, stability, electronic property, and growth pattern of gold clusters, which is very distinct from the case of 3d transition-metal-doped Au n clusters . Kumar et al carried out ab initio calculations on Gd-doped gold clusters and found a magic cage cluster Gd@Au 15 that has the attractive features of a large highest occupied molecular orbital–lowest unoccupied molecular orbital (HOMO–LUMO) gap and a great magnetic moment that could make it useful for both phototherapies of cancer cells as well as bioimaging .…”
Section: Introductionmentioning
confidence: 99%
“…During the last few decades, the binary clusters have attracted considerable attention of a wide range of researchers. Theoretical and experimental studies have demonstrated that the nature of the cluster can be altered significantly with the addition of a single impurity atom. , Doping of gold clusters with an impurity atom has been actively sought to tailor the desired structural, electronic, catalytic, and magnetic properties for potential applications in nanotechnology, microelectronics, solid-state chemistry, and materials science. For example, Zhang et al proved that doping with different 3p impurity atoms (Al, Si, P, S, and Cl) can strongly influence the structure, stability, electronic property, and growth pattern of gold clusters, which is very distinct from the case of 3d transition-metal-doped Au n clusters . Kumar et al carried out ab initio calculations on Gd-doped gold clusters and found a magic cage cluster Gd@Au 15 that has the attractive features of a large highest occupied molecular orbital–lowest unoccupied molecular orbital (HOMO–LUMO) gap and a great magnetic moment that could make it useful for both phototherapies of cancer cells as well as bioimaging .…”
Section: Introductionmentioning
confidence: 99%
“…The comparison between AlBe n and other Al-doped clusters shows how the relative size of impurity atom affects the structural evolution of the whole system. For example, the impurity Al atom always occupies an external position of the host clusters in AlBe n and AlB n [40] until n = 12, while it gets trapped in the host cage from n = 6 onwards in AlLi n [41] and AlNa n , [42,43] and fromn = 9 onwards in the AlTi n , [44] AlSc n , [45] AlPb n , [46] and AlY n [47] clusters. These structural distinctions can be related to the size difference of the dopant atom versus the host atom.…”
Section: Geometrical Structuresmentioning
confidence: 99%
“…However, of no less interest are the (pd)heterobimetallic metal clusters that include atoms of different categories of metals, namely, pand d-elements, since theoretically it can be expected that they will demonstrate such new properties that are not inherent to metal clusters containing metal atoms of only one category. These metal clusters, however, were considered in a much smaller number of works, in particular, in [51][52][53][54][55][56][57][58][59][60][61][62][63].Heterometallic metal clusters containing the atoms of those metals that are important in various fields of science and technology, namely aluminum and 3d elements (M), are very interesting objects from both a purely academic and practical points of view in this field. Some of them, in particular, Sc n Al, Y n Al, and Al n Ti, were considered in [58][59][60][61][62][63].…”
mentioning
confidence: 99%
“…However, of no less interest are the (pd)heterobimetallic metal clusters that include atoms of different categories of metals, namely, pand d-elements, since theoretically it can be expected that they will demonstrate such new properties that are not inherent to metal clusters containing metal atoms of only one category. These metal clusters, however, were considered in a much smaller number of works, in particular, in [51][52][53][54][55][56][57][58][59][60][61][62][63].…”
mentioning
confidence: 99%
See 1 more Smart Citation